(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
The researcher tried to show the importance of using environmental taxes as an effective economic factor for reducing contaminators resulting from cars exhausts, and presenting a suggested pattern for environmental taxes as a nucleus and a starting point for a wider implementing of environmental taxes in Iraq. In the theorytical aspect of this research, the researcher deals with the research problem, which is, the increasing size of environmental contaminators as a result of industrial and technical changes which covered all around the world, including Iraq , and the increasing size of cars exhausts contaminators .Ministry of Environment report for the year 2007 shows increasing rates of contaminators that resulting from cars exhausts which consist 60% of air contaminators. This research aims at activating the role of environmental taxes in handling the problem of cars exhausts contaminators, and putting a suggested pattern and working mechanism for imposing environmental tax on cars in Iraq. This research adopts the essential hypothesis which says ((Implementation of environmental tax on contaminators results a great positive impacts on the environmental level)).